Land Readjustment in Kathmandu Valley - Karmacharya, Sunaina (Journal of Science and Engineering, 2020)
Urban expansion of Kathmandu Valley is taking place at the fast rate challenging urban managers and planners of the city. In-migration has resulted in the unplanned urban growth of the city with the shortage of serviced land for urban development in Kathmandu. So Land Readjustment (LR) technique has been used as urban land development tool by the government. There are twenty two LR projects completed, and some of the projects are ongoing in the valley. The overview of the Land Readjustment technique of Kathmandu Valley has been done to explore the required measures needed to reform the existing legal and Institutional Framework and procedure of LR. Among the implemented LR projects, Nayabazar Land pooling has been selected for the case study as almost all the plots have been developed. Now, it is a dense residential neighborhood. The instruments used for research are literature study, in-depth interviews with different stakeholders of LR projects and landowners. Field visit and questionnaire survey in case study area are conducted regarding the street network and open space of the area. The existing system of LR technique is studied relating it with international experience mainly the case of Germany and Japan to draw positive inferences to explore the wider scope of LR technique for the comprehensive development in urban areas.